Clinical, dermoscopic and histopathologic features of genital and extragenital lichen sclerosus. (31st May 2012) - Larre Borges, A.; Tiodorovic‐Zivkovic, D.; Lallas, A.; Moscarella, E.; Gurgitano, S.; Capurro, M.; Apalla, Z.; Bruno, J.; Popovic, D.; Nicoletti, S.; Pérez, J.; Zalaudek, I.
Abstract Background Little is currently known about the dermoscopic patterns of genital and extragenital lichen sclerosus (LS). In order to evaluate and compare the dermoscopic and histopathologic patterns of genital and extragenital lichen sclerosus, a retrospective analysis of clinical, dermoscopic and histopathologic features of genital and extragenital LS, collected between March 2010 and December 2011 at four dermatology clinics in Greece, Italy, Serbia and Uruguay was performed. Observations A total of 29 lesions from 14 (mean age 62.8 years) and 12 (mean age 53.5 years) patients with genital and extragenital LS, respectively were analyzed. Mean duration of disease was 3.5 years for genital and 1.8 years for extragenital LS. White‐yellowish structureless areas were seen in all cases of genital and extragenital LS; however linear vessels occurred at higher frequency in genital than in extragenital lesions (85.7% vs. 33.3%, respectively). Extragenital LS revealed two different time‐related patterns: keratotic plugs were more prevalent in lesions with short duration (<2 years), whereas longer persisting lesions appeared atrophic and revealed fine chrysalis structures. Conclusions Our morphologic study provides novel insights into the morphologic diversity of LS at different body sites and different stages of progression.